Leptospira interrogans Secreted Proteases Degrade Extracellular Matrix and Plasma Proteins From the Host - da Silva, Ludmila B.; Menezes, Milene C.; Kitano, Eduardo S.; Oliveira, Ana K.; Abreu, Afonso G.; Souza, Gisele O.; Heinemann, Marcos B.; Isaac, Lourdes; Fraga, Tatiana R.; Serrano, Solange M. T.; Barbosa, Angela S. (Frontiers in Cellular and Infection Microbiology, 2018)
Leptospires are highly motile spirochetes equipped with strategies for efficient invasion and dissemination within the host. Our group previously demonstrated that pathogenic leptospires secrete proteases capable of cleaving and inactivating key molecules of the complement system, allowing these bacteria to circumvent host's innate immune defense mechanisms. Given the successful dissemination of leptospires during infection, we wondered if such proteases would target a broader range of host molecules. In the present study, the proteolytic activity of secreted leptospiral proteases against a panel of extracellular matrix (ECM) and plasma proteins was assessed. The culture supernatant of the virulent L. interrogans serovar Kennewicki strain Fromm (LPF) degraded human fibrinogen, plasma fibronectin, gelatin, and the proteoglycans decorin, biglycan, and lumican. Interestingly, human plasminogen was not cleaved by proteases present in the supernatants. Proteolytic activity was inhibited by 1,10-phenanthroline, suggesting the participation of metalloproteases. Moreover, production of proteases might be an important virulence determinant since culture-attenuated or saprophytic Leptospira did not display proteolytic activity against ECM or plasma components. Exoproteomic analysis allowed the identification of three metalloproteases that could be involved in the degradation of host components. The ability to cleave conjunctive tissue molecules and coagulation cascade proteins may certainly contribute to invasion and tissue destruction observed upon infection with Leptospira.